2022
DOI: 10.5194/hess-26-4013-2022
|View full text |Cite
|
Sign up to set email alerts
|

Flood forecasting with machine learning models in an operational framework

Abstract: Abstract. Google's operational flood forecasting system was developed to provide accurate real-time flood warnings to agencies and the public with a focus on riverine floods in large, gauged rivers. It became operational in 2018 and has since expanded geographically. This forecasting system consists of four subsystems: data validation, stage forecasting, inundation modeling, and alert distribution. Machine learning is used for two of the subsystems. Stage forecasting is modeled with the long short-term memory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in ungauged basins (PUB; e.g. Kratzert et al, 2019b;Prieto et al, 2019), transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2022;Nevo et al, 2022). Nonetheless, deep learning remains a field of progress with gaps to fill.…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in ungauged basins (PUB; e.g. Kratzert et al, 2019b;Prieto et al, 2019), transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2022;Nevo et al, 2022). Nonetheless, deep learning remains a field of progress with gaps to fill.…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…Five out of six studies evaluated neural network-based models, indicating that neural networks can be successful for this task. The other study, Nevo et al (2022), used a bespoke approach for their flood inundation modelling. No study tested alternative complex methods like random forests, so they provide no evidence about such methods.…”
Section: Previous Studies Evaluating ML On Extreme Eventsmentioning
confidence: 99%
“…To show how well ML-based systems perform in situations going beyond events seen in training, the most extreme events can be set aside in a second test dataset, as in Frame et al (2022) and Nevo et al (2022). This approach could be made even stronger by doing this before any model development is done, so the model structure and hyperparameters are chosen without being able to see the most extreme events beforehand.…”
Section: Ways Forwardmentioning
confidence: 99%
“…Second, to increase the lead time of the response, physically based models are used in the traditional framework for predictions. These systems consider different hydrological and inundation modeling components based on the specific target region, size of basins, available data and resources, and system development approach [ 19 ]. These physically based models considering detailed hydraulic processes (e.g., solving Saint-Venant equations) are complex and computationally intensive, causing limited applications in practical applications due to the availability of input data for parameterization and the detailed requirements of simulations [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%